Experimental Evaluation of Eco Sand as a Partial Replacement for Fine Aggregates in Mortar: A Sustainable Approach - U Din Dar, Hashim Mohi; Chauhan, Shilpa; ., Vishakha; Gupta, Vivek (AMC Indian Journal of Civil Engineering, 2025)
Fine aggregates function as structural fillers in mortar and concrete. Due to the diminishing availability of natural river sand and the rising demand for environmentally sustainable construction materials, alternative fine aggregate sources have become a major focus. The limited supply of river sand now significantly impacts both construction practices and the environment, driving the search for suitable replacements. One such alternative under consideration is eco sand, which is a byproduct of the cement manufacturing process. The physical properties of three different sands: river sand, manufactured sand, and eco sand were examined. The results showed that the particle size of eco sand was much smaller than others. The compressive strength of hardened mortar containing eco sand with river sand and manufactured sand increased with a decrease in percentage of eco sand. The workability showed a proportionate decrease with a percentage replacement of river sand and manufactured sand with eco sand. The compressive strength test indicates that replacement of fine aggregates can be done upto 40% without any decrease in strength while the strength being more than nominal mortar at 25% replacement. To sum up, this study gives a comparable level of performance and sustainability in managing waste materials, and it promotes resource conservation in the construction industry.